Peran Guru Bimbingan dan Konseling Dalam Kurikulum Merdeka (Penyusunan Asesmen Dan Modul Layanan) MGBK Kecamatan Cipayung Jakarta Timur - Julinda Siregar; Sahat T Simorangkir; Verry Jekson Panjaitan (CV. Multi Kreasi Media, 2025)
The purpose of this activity is to help Guidance and Counseling teachers in East Jakarta to be able to prepare assessments and service modules in the independent curriculum and to be able to accept every change with the aim of improving the quality of education. After the teachers attended the MGMP workshop on the role of guidance and counseling teachers in the independent curriculum, the PkM team conducted an interview with the Head of MGMP to find out the changes seen in the behavior of guidance and counseling teachers, especially in preparing service modules. The MGMP workshop went smoothly and the teachers were very happy and enthusiastic to listen to the presentation of material from the speakers. The Head of MGMP also explained that the teachers were happy with the PkM activities carried out by the Unindra Postgraduate Lecturer. The speaker explained that the independent curriculum is a curriculum that has been presented flexibly, and is implemented with a fun guidance and counseling service model that is prepared according to the content in the service program that has been prepared by guidance and counseling teachers in the service module. Furthermore, the speakers also said that in order to be able to innovate, guidance and counseling teachers must continue to develop themselves through training, seminars, workshops and also further studies.